Aerobic granular sludge treating hypersaline wastewater: Impact of pH on granulation and long-term operation at different organic loading rates. (15th March 2023) - Niu, Xueying; Han, Xushen; Jin, Yan; Yue, Jingxue; Zhu, Jingyi; Xie, Weihong; Yu, Jianguo
Abstract: pH is one of the major parameters that influence the granulation and long-term operation of aerobic granular sludge (AGS). In hypersaline wastewater, the impact of pH on granulation and the extent of organic loading rate (OLR) that AGS can withstand under different pH are still not clear. In this study, AGS was cultivated at 3% salinity in three sequencing batch reactors with influent pH values of 5.0, 7.0, and 9.0, respectively, and the OLR was stepwise increased from 2.4 to 16.8 kg COD/m 3 ·d after the granules maturation. The results showed the satisfactory granulation and organic removal under different influent pH conditions, in which the granulation was completed on day 43, 23, and 23, respectively. Neutral influent was the most appropriate for development of salt-tolerant aerobic granular sludge (SAGS), while acidic environment induced the formation of fluffy filamentous granules, and alkaline environment weakened the granule stability. Metagenomic analysis revealed the similar microbial community of neutral and alkaline conditions, with the predominance of genus Paracoccus_f__Rhodobacteraceae . While in acidic environment, fungus Fusarium formed the skeleton of filamentous granules and functioned as the carrier of bacteria including Azoarcus and Pararhodobacter . With the elevation of OLR, SAGSs were found to maintain the compact structure under OLRs of 2.4, 7.2, and 2.4 kg COD/m 3 ·d, and obtain high TOC removal (>95.0%) under OLRs of 7.2, 14.4, and 14.4 kg COD/m 3 ·d, respectively. For hypersaline high-strength organic wastewater, satisfactory TOC removal could also be obtained at broad pH ranges (5.0–9.0), in which neutral environment was the most suitable and acidic environment was the worst. This study contributed to a better understanding of SAGS granulation and treatment of hypersaline high-strength organic wastewater with different pH values. Graphical abstract: Image 1 Highlights: Granulation and high-strength wastewater treatment at varied pH were first studied. AGSs successfully formed in hypersaline wastewater with influent pH of 5, 7, and 9. Longer time was needed to form fluffy filamentous granules with influent pH of 5. SAGSs maintained compact under 2.4 (pH 5), 7.2 (pH 7), and 2.4 kg COD/m 3 ·d (pH 9). TOC removal was >95% under 7.2 (pH 5), 14.4 (pH 7), and 14.4 kg COD/m 3 ·d (pH 9).